17. Yüzyılın İkinci Yarısında Antakya Kazasında İskân ve Nüfus (1678/1089 Tarihli Avârız-Hâne Defterine Göre) - Çakar, Enver (Türk Tarih Kurumu [EN], 2004)
Osmanlı tarihinin temel kaynaklarının büyük çoğunluğunu vergi verebilecek nüfusun tespitini sağlayan ve sayım sonuçlarını içeren Tahrir Defterleri oluşturmaktadır. 15. ve 16. yüzyıllarda hazırlanmış olan, fakat 17. yüzyılda da bazı örneklerini gördüğümüz bu defterler, Osmanlı Devleti'nde timar sisteminin uygulandığı topraklardaki vergilendirilebilir ekonomik faaliyetlerin ve insan kaynaklarının yerinde tespit ve kaydını içermesi açısından bizlere istatistiksel analize uygun en zengin sayısal verileri sunmaktadırlar. Klasik tahrir geleneğinin bir uzantısı olarak 17. yüzyıldan itibaren düzenlenmiş olan avârız-hâne ve cizye defterleri de dönemin demografi tarihi açısından oldukça önemli kaynaklardır.

After the end of the classical Ottoman land register tradition, detailed avârız-hâne registers became very important sources as far as information concerning settlement areas within Ottoman lands and demographic movements in them, are concerned. Collecting population statistics by analysing these registers for each area will contribute enormously to the acquisition of credible data concerning changes in the demographic and settlement structures and the reasons underlying these changes. In this article we have studied in detail the settlement and population of the Antakya district in the second half of the 17th century, on the basis of the avârız-hâne register dated 1678. In that period the city of Antakya consisted of 24 neighbourhoods with 1.584 houses and 30 other public buildings with many houses, rooms and sheds. The majority of the population was Muslim, but there were also a small number of Christians who had settled there. In 1678, the villages of the district of Antakya were within the boundaries of four nahiye (subdivisions of a district), called Süveyde, Kuseyr, Cebel-i Akra and Altun Özü. The total of the villages was 153, with 127 of them being inhabited and 26 abandoned. The villages were inhabited by 3.512 adult males, of which 93 % were Muslim and 7 % non-Muslim. In general the population of the city of Antakya increased between the 16th and 17th centuries. The same is not true for its villages. Not only did the population of the villages diminish visibly, but there was also a decrease in the number of inhabited villages. Thanks to a policy of settlement support, many villages were settled once more towards the end of the 17th century.
Settlement and Population in the District of Antakya, During the Second Half of the 17TH Century [According to the Avârız-Hâne (Household Tax) Register, dated 1678/1089]